A comprehensive study of the life cycle of a South-American population of Stigeoclonium tenue (Chaetophorales, Chlorophyta) - Michetti, Karina Mariel (2010)
The diplobiontic–haplodiplontic life cycle with alternating isomorphic generations in Stigeoclonium tenue (C. Agardh) Kütz. is described for the first time. Sporophytes (2n = 10) arise from tetraflagellate zoospores that are produced by meiosis. Sporic meiosis might be inferred from the cruciform divisions formed during zoosporogenesis and is confirmed through observations of prophase I substages. Zoospores do not germinate directly but produce a haploid cyst that germinates to give rise to a gametophyte (n = 5). Gametophytes produce biflagellate isogametes, which fuse to produce zygotes that germinate by mitosis into the sporophytic stage. Gametophytes and sporophytes reproduce asexually both via mitotic tetraflagellate zoospores and by thallus fragmentation. Results from this study indicate that both the cosmopolitan distribution and dominance of S. tenue in many periphytic communities might be due to its multiple reproductive strategies.